2014
DOI: 10.1016/j.cct.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Making healthy eating and physical activity policy practice: The design and overview of a group randomized controlled trial in afterschool programs

Abstract: National and state organizations have developed policies calling upon afterschool programs (ASPs, 3-6pm) to serve a fruit or vegetable (FV) each day for snack, while eliminating foods and beverages high in added-sugars, and to ensure children accumulate a minimum of 30 min/d of moderate-to-vigorous physical activity (MVPA). Few efficacious and cost-effective strategies exist to assist ASP providers in achieving these important public health goals. This paper reports on the design and conceptual framework of Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 76 publications
(142 reference statements)
1
56
0
Order By: Relevance
“…A complete description and overview of the study can be found elsewhere [12]. For this study, ASPs were defined as child care programs operating immediately after the school day, every day of the school year for a minimum of 2 h. Programs had to serve a minimum of 30 children of elementary age (6-12 years) and could operate in a school, community, or faith setting.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A complete description and overview of the study can be found elsewhere [12]. For this study, ASPs were defined as child care programs operating immediately after the school day, every day of the school year for a minimum of 2 h. Programs had to serve a minimum of 30 children of elementary age (6-12 years) and could operate in a school, community, or faith setting.…”
Section: Methodsmentioning
confidence: 99%
“…All children enrolled, staff, and ASP leaders in the programs were eligible to participate in the study. A total of 20 ASPs, representing 13 different organizations were randomly selected from an existing registry of 535 ASPs in South Carolina and invited to participate in an intervention targeting healthy eating and physical activity -Making Healthy Eating and Physical Activity Policy Practice [12]. Of the 535 programs, 376 met the eligibility criteria-76 did not operate Mon-Fri, 53 enrolled fewer than 30 children, and 30 did not have sufficient information to evaluate eligibility.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations